Nitric Oxide Primes Pancreatic β Cells for Fas-mediated Destruction in Insulin-dependent Diabetes Mellitus - Stassi, Giorgio (The Rockefeller University Press, 1997)
Fas is an apoptosis-inducing surface receptor involved in controlling tissue homeostasis and function at multiple sites. Here we show that β cells from the pancreata of newly diagnosed insulin-dependent diabetes mellitus (IDDM) patients express Fas and show extensive apoptosis among those cells located in proximity to Fas ligand–expressing T lymphocytes infiltrating the IDDM islets. Normal human pancreatic β cells that do not constitutively express Fas, become strongly Fas positive after interleuken (IL)-1β exposure, and are then susceptible to Fas-mediated apoptosis. N(G)-monomethyl-l-arginine, an inhibitor of nitric oxide (NO) synthase, prevents IL-1β–induced Fas expression, whereas the NO donors sodium nitroprusside and nitric oxide releasing compound (NOC)-18, induce functional Fas expression in normal pancreatic β cells. These findings suggest that NO-mediated upregulation of Fas contributes to pancreatic β cell damage in IDDM.